2013
DOI: 10.1007/s00018-013-1521-z
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate transporters in the biology of malignant gliomas

Abstract: Malignant gliomas are relentless tumors that offer a dismal clinical prognosis. They develop many biological advantages that allow them to grow and survive in the unique environment of the brain. The glutamate transporters System xc− and Excitatory Amino Acid Transporters (EAAT) are emerging as key players in the biology and malignancy of these tumors. Gliomas manipulate glutamate transporter expression and function to alter glutamate homeostasis in the brain, which supports their own growth, invasion, and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 173 publications
0
84
0
1
Order By: Relevance
“…1 Under such conditions, astrocytes, the main glutamate scavengers, may no longer suffice to alleviate the neurotoxic levels of extracellular glutamate. The response of TAMs, consisting of both parenchymal microglia and peripheral macrophages recruited to the brain, to the excess of glutamate released by tumor cells is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Under such conditions, astrocytes, the main glutamate scavengers, may no longer suffice to alleviate the neurotoxic levels of extracellular glutamate. The response of TAMs, consisting of both parenchymal microglia and peripheral macrophages recruited to the brain, to the excess of glutamate released by tumor cells is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of glutamate signaling in the central nervous system is known to be a key factor in the invasion and growth of glioblastoma 1 and in induction of seizures. 2 Glioblastoma cells secrete high levels of glutamate into the extracellular milieu, triggering neuronal cell death through the over-excitation of glutamate receptors and subsequently providing more space for glioblastoma cells to invade and expand.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In exchange for cystine uptake, this antiporter releases intracellular glutamate which impacts on multiple aspects of glioma biology. 11,12 As such, glutamate reportedly promotes glioma cell growth 13 and has been linked to tissue destruction 14 and tumorassociated epilepsy. 15 Studies in glioma cells have shown that system X c − is upregulated under oxidative stress, 16 and Takeuchi et al 17 reported that increased X c − expression in human GBMs was associated with a shorter survival.…”
Section: Introductionmentioning
confidence: 99%
“…However, TMZ increased glutamate release from glioma cells and the co-incubation with GUO prevented this increase. It is well described that the high extracellular glutamate levels released by glioma cells can lead to excitotoxic neuronal death and improve tumor viability, progression, and aggressiveness [43]. In this sense, the increase in glutamate release could be a possible aggravating factor of TMZ side effects, if it occurs in vivo.…”
Section: Discussionmentioning
confidence: 99%